Perbandingan Metode SMART Dan SAW Dalam Menentukan Karyawan Terbaik - Sari, Dian Permata (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Employee performance appraisal to select the best employees in an agency is very important. Giving awards for performance is a form of company appreciation to employees and a motivation for other employees to work seriously. However, the assessment is not objective, meaning that it does not have a standard assessment standard. To assist companies in determining the best employees, a decision support system (SPK) can be one of the solutions by calculating based on criteria determined by the company. For this case, the authors apply the SAW and SMART methods which are part of the DSS method in solving problems. There are several variables used, namely discipline, attendance, loyalty, teamwork, and performance. To obtain the final result, both SAW and SMART methods are calculated, then the results will be ranked, the one with the highest score becomes the main candidate in selecting the best employee.